2014
DOI: 10.1021/bm401926k
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Cocultures with Endothelial Cells and Fibroblasts on Micropatterned Fibrous Mats to Promote Liver-Specific Functions and Capillary Formation Capabilities

Abstract: The maintenance of hepatocyte phenotype and functions remains as a great challenge in the generation of functional liver tissue and in vitro model for drug metabolism studies. The use of hepatocyte coculture systems plays essential roles in the establishment of cell-cell and cell-extracellular matrix communications similar to native liver tissues. In the current study, micropatterned electrospun fibrous mats were created to load hepatocytes, fibroblasts, and endothelial cells (ECs), which were precisely assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 41 publications
2
66
0
Order By: Relevance
“…Conversely, we also investigated whether hPSC‐ECs could, in turn, impact the metabolic function of hPSC‐HEPs in a coculture setting. It has been reported that endothelial cells could improve hepatic function [] and provide some levels of hepatoprotection from acetaminophen toxicity []. In our study, cocultured hPSC‐HEPs had comparable albumin levels with monocultured hPSC‐HEPs (supplemental online Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Conversely, we also investigated whether hPSC‐ECs could, in turn, impact the metabolic function of hPSC‐HEPs in a coculture setting. It has been reported that endothelial cells could improve hepatic function [] and provide some levels of hepatoprotection from acetaminophen toxicity []. In our study, cocultured hPSC‐HEPs had comparable albumin levels with monocultured hPSC‐HEPs (supplemental online Fig.…”
Section: Resultssupporting
confidence: 64%
“…Continuous replenishment of metabolites in coculture setup recapitulated the systemic setting of liver paracrine effects on the vasculatures. Conversely, endothelial cells are known to improve hepatic function by promoting cell viability, synthesis of albumin and urea, and efficiency of the drug transporter system []. Our hPSC‐ECs could, in turn, increase the metabolizing CYP enzyme activity in hPSC‐HEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of endothelial cells (ECs) has already been shown in the formation of various organs such as heart[13], liver[47], kidney[8], bone[9], and skin among many others[1013]. Thus, efficient EC preparation methods that provide scalable and stable supply are necessary for three-dimensional (3D) tissue engineering and organ regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional stacked polycarbonate membranes with hepatocytes showed functional liver units in vitro [143]. Functional liver units were also observed using micropatterned Poly(ethylene glycol)-poly(dl-lactide) and lactosylated poly(dl-lactide) electrospun fibrous mats [144]. For larger structures, like the bile duct or vascular structures, polymers may be formed into sheets and then tube structures.…”
Section: Naturally-derived and Synthetic Polymer Strategies For Largementioning
confidence: 82%